Content And Nature Of The Service Economy - Sherqulov Dilshod Juraqulovich (Genius Journals, 2022)
This article provides information on the meaning and essence of the service economy, the priority of service in the economies of countries that have transitioned to a market economy, and the fact that service industries are a component of the country's economy
Keywords: Service; diversification; economy; exchange